IMPACT OF E.U. FUNDING ON RURAL AND REGIONAL DEVELOPMENT MANAGEMENT - Berislav ANDRLIC; Marko SOSTAR; Tatjana BODEGRAJAC (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
EU funds are all financial and operative programs funded by the European Union, either in the Member States (Union Programs and instruments of the Cohesion, Agriculture and Fisheries Policies), or outside of them (preaccession funds, other country programmes). In order to develop the regions, cities and villages of Croatia, the programme of strategic investment is established by the regional policy which promotes economic and social growth and improves the living standard. It gives support for less developed areas and rural regions as an expression of solidarity. Purpose of this research paper is to identify level of knowledge about EU funds in rural area with survey method. There is a practical example of a survey of the respondents on the impact of EU funds on reducing rural regional inequalities as a result of this paper.